Preschool mother-child emotional preparation program leads to significant improvement in autonomic regulation: a randomized controlled trial - Welch, Martha G.; Ludwig, Robert J.; Kong, Justin; Rauh, Virginia; Hane, Amie A.; Jaffe, Marc; Witkowski, Anna; Myers, Michael M. (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction Many studies have documented the profound impact that the mother-child relationship has on child sociality and behavior. However, the biological mechanisms that govern the relationship are poorly understood. We developed a mother-child emotional preparation program (MCEP), based on a novel autonomic nervous system learning mechanism. MCEP is hypothesized to condition the child's autonomic nervous system to better meet the preschool socioemotional classroom challenges. Methods We conducted a randomized controlled trial of MCEP, comparing a group of children receiving standard curriculum with children receiving standard curriculum plus MCEP. Previously, we reported that the MCEP mother-child dyads (vs controls) were more emotionally connected at six months post intervention and MCEP children (vs controls) displayed better socioemotional behavior at home and in the classroom. At six months post intervention, mothers and children underwent a stressful interaction-interruption paradigm, during which we acquired child ECG. We analyzed heart rate and several measures of child heart rate variability obtained during the 10-minute post-stress recovery period. Results We found that MCEP children showed better autonomic regulation following the stressor, as measured by lower heart rate (p = 0.017) and increased high frequency respiratory sinus arrhythmia (RSA) or vagal tone (p = 0.043). Surprisingly, despite a sample size limited by COVID (n = 12 and 12), the effect sizes were large (g's ranging from 0.89 to 1.09). In addition, we found significant correlations with large effect sizes between autonomic measures and scores on the Welch Emotional Connection Screen (WECS). Discussion These findings support the conclusion that MCEP had a significant positive impact on child autonomic regulation in response to stress, which correlates with behavioral assessments of emotional connection. We discuss theoretical considerations and the implications of our findings for preschool education programs in general. This trial was retrospectively registered (clinicaltrial.gov registry NCT02970565) three months after the start of the first recruitment on April 9, 2019.